Cavernous Hemangioma of the Tongue - Krishna Kripal; Senthil Rajan; Beena Ropak; Ipsita Jayanti (Hindawi Limited, 2013)
Hemangioma is a benign tumor of dilated blood vessels. It is most commonly seen in the head and neck region and rarely in the oral cavity. Hemangiomas in the oral cavity are always of clinical importance and require appropriate treatment. We report here a case of a 34-year-old female patient with a swelling on the lateral surface of tongue which did not respond to the sclerosing agent and was finally confirmed as cavernous hemangioma on histological evaluation.